The ideal cardiovascular health metrics associated inversely with mortality from all causes and from cardiovascular diseases among adults in a Northern Chinese industrial city. - Yan Liu; Hong-jie Chi; Liu-fu Cui; Xin-chun Yang; Yun-tao Wu; Zhe Huang; Hai-yan Zhao; Jing-sheng Gao; Shou-ling Wu; Jun Cai (PLoS ONE)
Background and aims The American Heart Association has recently established seven ideal cardiovascular health metrics for cardiovascular health promotion and disease reduction (i.e., non-smoking, normal body mass index, physically active, healthy diet, and normal levels of cholesterol, blood pressure and fasting blood glucose). The present study seeks to evaluate how well these metrics predict mortality from all causes and cardiovascular diseases in adult Chinese living in a northern industrial city. Methods and results Data of 95,429 adults who participated in the Kailuan cohort study from June 2006 to October 2007 was analyzed. All participants underwent questionnaire assessment, clinical examination, laboratory assessments and were followed up biannually. During a median follow-up of 4.02 years, 1,843 deaths occurred, with 597 deaths resulting from cardiovascular diseases. Lower mortality rates from all causes and cardiovascular diseases were observed among the subjects who met a higher number of the ideal health metrics. Compared to the participants who met none or one ideal health metric, those meeting ≥5 ideal health metrics had a lower risk of all-cause mortality by 30% (adjusted hazard ratio, 0.70; 95% confidence interval, 0.56-0.88) and a lower risk of mortality from cardiovascular diseases by 39% (adjusted hazard ratio, 0.61; 95% confidence interval, 0.41-0.89) . Four metrics (smoking status, physical activity, blood pressure and fasting blood glucose) were significantly associated with all-cause mortality. Three metrics (physical activity, blood pressure and fasting blood glucose) were significantly associated with mortality from cardiovascular diseases. Conclusion The number of ideal health metrics is negatively associated with mortality rates from all causes and cardiovascular diseases among adults in a Northern Chinese industrial city. The data supports the AHA recommendation of ideal health metrics for adults from Northern China.